Coal gangue-based composite fluorine removal agent as well as preparation method and application thereof
By loading boehmite on coal gangue, a composite fluorine removal agent of coal gangue is prepared, which solves the problems of low fluorine ion removal efficiency and high cost in the prior art, and achieves a high-efficiency and low-cost deep fluorine ion defluorination effect.
Patent Information
- Application Number
- CN202411985226.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing high-concentration fluorine ion removal technology cannot effectively reduce the fluorine ion concentration to less than 1.5 mg/L, and aluminum (hydrogen) oxides as adsorbents have problems of high cost and easy agglomeration.
Coal gangue is used as a carrier to load boehmite by co-precipitation method to prepare a composite fluorine-removing agent based on coal gangue, which reduces the agglomeration of boehmite and improves its dispersion.
It effectively reduces the production cost of fluorine defluoride, improves the deep defluorination efficiency of fluorine ions, and when treating fluorine-containing wastewater, the fluorine ion concentration can be reduced to below 1 mg/L, meeting the drinking water standards.
Smart Images

Figure CN119657069A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of defluorination materials, and specifically relates to a gangue-based composite defluorination agent and a preparation method and application thereof. Background Art
[0002] Fluoride is a trace element. Drinking water with a fluoride content of 0.4-0.6 mg / L is harmless and beneficial to the human body. However, long-term drinking of high-fluoride water with a fluoride content greater than 1.5 mg / L will have adverse effects on the human body, and in severe cases will cause fluorosis and fluorosis of the bones. With the rapid development of emerging industries such as semiconductors and solar energy, the discharge of fluoride-containing wastewater has increased year by year, which has posed a severe challenge to human survival and safety. Therefore, fluoride-containing wastewater must be treated.
[0003] The high-concentration fluoride ion removal technology currently in practical use is mainly the pharmaceutical method, but it can usually only treat fluoride ions to about 10 mg / L, which is much higher than the 1.5 mg / L drinking water standard set by the World Health Organization. In order to obtain low-fluoride water, the water pre-treated by the pharmaceutical method needs to be further deeply defluorinated. Among various methods, the adsorption method has a simple process, easy operation, and low cost, and has attracted much attention. Among them, the development of efficient and low-cost fluoride ion adsorption materials is the key to achieving deep defluorination.
[0004] Aluminum (hydroxide) oxides such as boehmite AlOOH and γ-alumina have high specific surface area and good defluorination performance and are often used as defluorination materials. However, their high synthesis cost and easy agglomeration disadvantages limit their practical application effects. Summary of the invention
[0005] In view of the above problems, the present invention provides a gangue-based composite defluorinating agent and a preparation method thereof. The present invention uses gangue as a carrier, loads boehmite on the surface of gangue by a simple coprecipitation method, and obtains the gangue-based composite defluorinating agent after drying. The problem of high defluorination cost and easy agglomeration when aluminum (hydroxide) oxide is used as an adsorbent alone is effectively solved.
[0006] The first object of the present invention is to provide a method for preparing a coal gangue-based deep defluorination agent, which is characterized by comprising the following steps:
[0007] The gangue is mixed with an alkali metal chloride aqueous solution to obtain a suspension, a soluble aluminum salt solution is added at 50-95°C, the pH value is controlled to be 8-11, a coprecipitation reaction occurs, and a gangue-based composite defluoridating agent in which boehmite is loaded on the gangue is obtained.
[0008] When adding soluble salt, the temperature is 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, etc., but is not limited to the listed values, and other values not listed in the above numerical range are also applicable. Further, the concentration of the alkali metal chloride aqueous solution is 0.2g / ml. Further, the temperature is 80°C.
[0009] The pH value is 8, 9, 10, 11, etc., but is not limited to the values listed above. Other values not listed in the above range are also applicable. If the alkalinity is too strong, boehmite will be formed before loading, which is not conducive to loading on coal gangue.
[0010] As a preferred embodiment, the concentration of the alkali metal chloride aqueous solution is 0.01 g / ml to 0.2 g / ml. For example, the concentration of the alkali metal chloride aqueous solution is 0.01 g / ml, 0.02 g / ml, 0.04 g / ml, 0.06 g / ml, 0.08 g / ml, 0.1 g / ml, 0.12 g / ml, 0.14 g / ml, 0.16 g / ml, 0.18 g / ml, 0.2 g / ml, etc., but is not limited to the listed values, and other values not listed in the above numerical range are also applicable. Further, the concentration of the alkali metal chloride aqueous solution is 0.2 g / ml.
[0011] As a preferred embodiment, the solid-liquid ratio of coal gangue to alkali metal chloride aqueous solution is (0.2g-5g):30ml. For example, the solid-liquid ratio of coal gangue to alkali metal chloride aqueous solution is 0.2g:30ml, 0.8g:30ml, 1.4g:30ml, 2g:30ml, 2.6g:30ml, 3.2g:30ml, 3.8g:30ml, 4.4g:30ml, 5g:30ml, etc., but it is not limited to the listed values, and other unlisted values within the above numerical range are also applicable. Further, the solid-liquid ratio of coal gangue to alkali metal chloride aqueous solution is 1g:30ml.
[0012] As a preferred embodiment, the concentration of aluminum ions in the soluble aluminum salt solution is 10mol / ml to 100mol / ml. For example, the concentration of aluminum ions in the soluble aluminum salt solution is 10mol / ml, 20mol / ml, 30mol / ml, 40mol / ml, 50mol / ml, 60mol / ml, 70mol / ml, 80mol / ml, 90mol / ml, 100mol / ml, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable. Further, the concentration of aluminum ions in the soluble aluminum salt solution is 40mol / ml.
[0013] As a preferred embodiment, the volume ratio of the alkali metal chloride aqueous solution to the soluble aluminum salt solution is 1:1.
[0014] As a preferred embodiment, the coprecipitation reaction time is 10min to 4h. For example, the coprecipitation reaction time is 10min, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, but it is not limited to the listed values, and other values not listed in the above numerical range are also applicable. Further, the coprecipitation reaction time is 2h.
[0015] As a preferred embodiment, the soluble aluminum salt is one or more of aluminum sulfate, aluminum nitrate, aluminum chloride, and alum.
[0016] As a preferred embodiment, the alkali metal chloride salt is one of potassium chloride, sodium chloride and lithium chloride.
[0017] The second object of the present invention is to provide a gangue-based composite defluorinating agent prepared by the above preparation method.
[0018] The third object of the present invention is to provide an application of the above-mentioned coal gangue-based composite defluorinating agent in the treatment of fluoride-containing wastewater, characterized in that the concentration of fluoride ions in the fluoride-containing wastewater is 1.5 mg / L to 10 mg / L, and the addition amount of the coal gangue-based composite defluorinating agent is 0.5 g / L to 1 g / L.
[0019] As a preferred embodiment, the pH value of the fluorine-containing water is 3 to 3.5.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention provides a method for preparing a gangue-based composite defluorinating agent, which uses only conventional soluble aluminum salts, alkali metal chlorides and gangue solid waste as reaction reagents and raw materials, without using other expensive reagents and artificial synthetic carriers. The preparation method is simple and does not require special equipment, which effectively reduces the production cost. During the preparation process, the pH of the system is adjusted to 8-11, and a coprecipitation reaction occurs, which is beneficial to the reaction of chloride ions with Al 3+ Boehmite precursors, i.e., [AlCl4]-ligands, are preferentially generated, which slowly hydrolyze to generate boehmite, facilitating migration to the surface of coal gangue to form a load; on the other hand, a system pH of 8 to 11 can increase the viscosity of the solution, reduce the continuity of boehmite, facilitate the formation of a multi-level nanostructure, and increase the number of adsorption active sites. Therefore, using coal gangue as a carrier can effectively improve the dispersibility of boehmite and reduce agglomeration. Compared with pure boehmite, the amount of boehmite in the coal gangue-based composite defluoridation agent is reduced, so the price of the defluoridation agent per unit mass is reduced.
[0022] (2) The present invention provides a gangue-based composite defluorinating agent, which uses solid waste gangue as a carrier, which can effectively improve the dispersibility of boehmite particles and enhance their defluorination efficiency; the loaded boehmite is in a multi-layered network, which is beneficial to the improvement of adsorption capacity; in addition, small-sized boehmite is anchored on the surface of large-sized gangue particles, and the recyclability is greatly improved.
[0023] (3) The present invention provides a coal gangue-based composite defluoridation agent, which can deeply defluorinate fluoride-containing wastewater with a fluoride ion concentration of less than 10 mg / L to below 1 mg / L; the defluoridation process is less interfered by coexisting anions such as nitrate, carbonate, bicarbonate and sulfate, and has excellent selectivity; in addition, the defluoridation agent causes little additional pollution during actual use, and the Pb content in the aqueous solution after defluoridation is lower than the minimum limit of the national standard. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The X-ray diffraction patterns of the gangue-based composite defluorinating agent, gangue and boehmite prepared in Example 1 are as follows:
[0025] Figure 2 The scanning electron microscope images are of coal gangue and the coal gangue-based composite defluorinating agent prepared in Example 1. Among them, a is coal gangue at a scale of 5 μm, b is coal gangue at a scale of 500 nm, c is coal gangue-based composite defluorinating agent at a scale of 5 μm, and d is coal gangue-based composite defluorinating agent at a scale of 500 nm.
[0026] Figure 3 The scanning electron microscope images and corresponding energy spectrum result images of coal gangue and the coal gangue-based composite defluorinating agent prepared in Example 1. Among them, a is a partial scanning morphology of coal gangue and a distribution ratio of elements corresponding to a rectangular sampling frame, and b is a partial scanning morphology of coal gangue-based composite defluorinating agent and a distribution ratio of elements corresponding to a rectangular sampling frame.
[0027] Figure 4 This is a comparison chart of the defluorination efficiency of the gangue-based composite defluorination agent prepared in Example 1 and the gangue at different addition amounts.
[0028] Figure 5 This is a comparison chart of the fluorine removal efficiency of the gangue-based composite defluorinating agent and gangue prepared in Example 1 of the present invention at different pH values.
[0029] Figure 6 The defluorination efficiency and equilibrium adsorption capacity of the gangue-based composite defluorination agent prepared in Example 1 at different addition amounts.
[0030] Figure 7 This is a diagram showing the effect of coexisting anions on the defluorination efficiency of the gangue-based composite defluorination agent prepared in Example 1.
[0031] Figure 8The fluorine removal efficiency and the content of aluminum (hydroxide) loaded of the fluorine removal agents prepared in different embodiments and comparative examples are shown. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention provides a method for preparing a gangue-based composite defluorinating agent, comprising the following steps:
[0034] The gangue is mixed with an alkali metal chloride aqueous solution to obtain a suspension, a soluble aluminum salt solution is added at 50-95°C, the pH value is controlled to be 8-11, a coprecipitation reaction occurs, and a gangue-based composite defluoridant in which boehmite is loaded on the gangue is obtained.
[0035] Coal gangue acts as a carrier. Through its surface structure, in an alkaline environment, the chloride ions in the alkali metal chloride salt react with the aluminum ions in the soluble aluminum salt to generate [AlCl4] - Ligands are used to generate boehmite on the surface of coal gangue. The boehmite nucleated and grown on the surface of coal gangue forms a nano multi-level network structure, which can increase the number of adsorption active sites, thereby improving the adsorption efficiency of the surface-loaded boehmite. Therefore, in the coal gangue-based composite defluoridation agent provided by the present invention, only a small amount of surface-loaded boehmite can achieve the effect of pure boehmite and commercial alumina.
[0036] Changing the amount of each raw material added and the preparation parameters will affect the boehmite loading and distribution morphology. If there is too little boehmite on the surface of the gangue, there will be fewer adsorption sites; if there is too much boehmite on the surface of the gangue, the boehmite near the surface of the gangue will not work. In addition, the amount of each raw material added and the preparation parameters will also affect whether the gangue-based composite defluorination agent forms a multi-level nanostructure, which will affect the activity to a certain extent.
[0037] The present invention has no particular limitation on the selection of the soluble aluminum salt, and any conventional soluble aluminum salt known to those skilled in the art can be used. Those skilled in the art can select and adjust the soluble aluminum salt according to actual application conditions, product quality and product performance. Preferably, the soluble aluminum salt used in the present invention is one or more of aluminum sulfate, aluminum nitrate, aluminum chloride and alum.
[0038] The present invention has no particular limitation on the selection of the alkali metal chloride salt, and any conventional alkali metal chloride salt known to those skilled in the art can be used. Those skilled in the art can select and adjust the alkali metal chloride salt according to actual application conditions, product quality and product performance. The alkali metal chloride salt is one of potassium chloride, sodium chloride and lithium chloride.
[0039] The coal gangue used in the present invention comes from Huainan, Anhui Province, and its mineral composition is shown in Table 1. When used, the particle size of the coal gangue is 800 meshes.
[0040] Table 1 Main mineral composition of coal gangue
[0041] Mineral composition quartz Kaolinite muscovite Gray matter Content (wt.%) 56.0% 9.2% 12.2% 22.6%
[0042] The gangue-based composite defluorinating agent prepared by the invention can be used for treating fluoride-containing wastewater.
[0043] Example 1
[0044] Preparation of coal gangue-based composite defluoridation agent:
[0045] 5g of coal gangue was mixed with 150ml of 0.02g / ml sodium chloride aqueous solution to obtain a suspension, which was heated to 80°C; 150ml of 20mmol / L aluminum nitrate solution was dripped into the suspension, while the pH value was controlled to 8, and a coprecipitation reaction was performed for 2h; after centrifugation, washing and drying, a coal gangue-based composite defluoridant was obtained, which was recorded as GA8.
[0046] Example 2
[0047] 5g of coal gangue was mixed with 150ml of 0.01g / ml sodium chloride aqueous solution to obtain a suspension, which was heated to 50°C; 150ml of 5mmol / L aluminum sulfate solution (Al 3+ The concentration of 10 mol / ml) was dropped into the suspension, and the pH value was controlled to be 8, and a coprecipitation reaction was carried out for 4 hours; after centrifugation, washing and drying, a coal gangue-based composite defluoridating agent was obtained.
[0048] Example 3
[0049] 25g of coal gangue was mixed with 150ml of 0.2g / ml potassium chloride aqueous solution to obtain a suspension, which was heated to 95°C; 150ml of 100mmol / L alum solution (Al 3+ The concentration of 100 mol / ml) was dropped into the suspension, and the pH value was controlled to be 11, and a coprecipitation reaction was carried out for 10 minutes; after centrifugation, washing and drying, a coal gangue-based composite defluoridating agent was obtained.
[0050] Comparative Example 1
[0051] 150 ml of 0.02 g / ml sodium chloride aqueous solution was mixed to obtain a suspension, which was heated to 80° C. 150 ml of 20 mmol / L aluminum nitrate solution was dropped into the suspension, while the pH value was controlled to 8, and a coprecipitation reaction was performed for 2 hours. Boehmite was obtained after centrifugation, washing, and drying, and was recorded as A8.
[0052] Figure 1 It is the X-ray diffraction (XRD) pattern of the gangue-based composite defluoridation agent (GA8), gangue (G) and boehmite (A8) prepared in Example 1, wherein the synthesis conditions of boehmite are the same as those of GA8 but without the addition of gangue. It can be seen that gangue is mainly composed of kaolinite (K) and a small amount of quartz (Q) and muscovite (M) impurities; the XRD diffraction pattern of the gangue-based composite defluoridation agent (GA8) has a new peak near 27.6° compared to pure gangue, corresponding to boehmite, but the weak peak intensity indicates that the loading is less. The reference sample without the addition of gangue presents a typical boehmite (A8) feature, and its main diffraction peaks can be clearly distinguished. Since gangue does not dissolve and only acts as a matrix, the XRD results prove that in the GA8 obtained in Example 1, if the aluminum element can be loaded on gangue, it exists in the form of boehmite.
[0053] Figure 2 The following are scanning electron microscope images of coal gangue (G) and the coal gangue-based composite defluorinating agent (GA8) prepared in Example 1. Figure 2 As can be seen from a and b in the figure, the coal gangue mainly presents a smooth flaky morphology; Figure 2 From c and d, it can be clearly seen that a multi-level network structure has been newly added to the surface of the coal gangue. The emergence of this structure is conducive to improving the adsorption capacity.
[0054] Figure 3 The scanning electron microscope images and corresponding energy spectrum results of coal gangue (G) and the coal gangue-based composite defluorination agent (GA8) prepared in Example 1 are shown. The interference of C and O in the conductive glue and residual atmosphere is not considered, and the Si element in the coal gangue is used as a reference. Figure 3 The Al / Si atomic ratio in the composite defluoridation agent for coal gangue was found to be 1.44, which was significantly higher than 0.83 in coal gangue ( Figure 3 a), indicating that the newly added multi-layered mesh material on the surface of coal gangue is aluminum-containing compounds, combined with Figure 1 The XRD results show that it is boehmite.
[0055] In order to further demonstrate the defluorination efficiency of the gangue-based composite defluorination agent (GA8) of the present invention, a defluorination test was performed on the gangue-based composite defluorination agent prepared in Example 1.
[0056] Fluoride-containing wastewater was subjected to the following operation: 10 mg / L NaF aqueous solution was prepared, the pH of the solution was adjusted by dropping 1M NaOH or 1M HCl solution, and then a gangue-based composite defluoridation agent was added for adsorption experiment. Next, the amount of gangue-based composite defluoridation agent added, the pH of fluoride-containing wastewater, and different concentrations of acid anions were changed to conduct adsorption experiments to investigate the adsorption capacity of the defluoridation agent. After the adsorption experiment, the supernatant was centrifuged and separated, and the remaining fluoride ion concentration in the solution was tested with a fluoride ion meter.
[0057] Firstly, under the conditions of defluorination time of 6h, temperature of 30℃, initial concentration of fluoride solution C0 of 10mg / L, and pH of 3.5, the addition amount of gangue-based composite defluorination agent was changed to investigate the effect of the gangue-based composite defluorination agent on the defluorination efficiency. Figure 4 As shown in the figure, at different addition amounts, the fluorine removal rate of GA8 is much higher than that of coal gangue.
[0058] Under the conditions of 0.5 g / L defluoridation agent dosage, 6 h defluoridation time, 30 °C temperature, and 10 mg / L initial fluoride ion solution concentration C0, the pH value of fluoride-containing wastewater was changed to investigate the effect of pH value of fluoride-containing wastewater on defluoridation efficiency. Figure 5 As shown, it can be seen that the adsorption rate of fluoride ions is the highest when pH = 3. Because too high an adsorption rate is not conducive to studying the influence of various factors on the adsorption performance of the sample, pH = 3.5 is selected when studying the influence of other factors, and pH = 3 is selected when studying the optimal adsorption performance.
[0059] Under the conditions of defluorination time of 6h, temperature of 30℃, initial concentration of fluoride solution C0 of 10mg / L, and pH of 3.5, the defluorination efficiency and equilibrium adsorption capacity at different defluorination agent addition amounts are as follows: Figure 6 As shown in the figure, it can be seen that the fluorine removal efficiency is the lowest when the lowest dosage of the gangue-based composite defluorinator is 0.125 g / L. As the dosage increases to 1 g / L, the fluorine removal efficiency increases, mainly because the adsorption active sites increase with the increase of the adsorption dosage; and when it further increases to 3 g / L, the adsorption efficiency gradually decreases, which may be caused by the excessive amount of defluorinator causing the particle overlap phenomenon to intensify. Equilibrium adsorption capacity q e It is gradually decreasing. The main reason is that as the number of defluoridation agents increases, the number of active sites also increases. However, the concentration of fluoride ions in the solution is constant, so the equilibrium adsorption capacity gradually decreases. In studying the influence of other factors, in order to take into account both the fluoride ion removal rate and the equilibrium adsorption capacity, the dosage of the gangue-based composite defluoridation agent is 0.5 mg / L; and when studying the optimal adsorption rate, the dosage of the gangue-based composite defluoridation agent is 1 mg / L.
[0060] Under the conditions of 0.5 g / L defluoridation agent dosage, 6 h defluoridation time, 30 °C temperature, 10 mg / L initial concentration of fluoride solution C0, and pH 3.5, different concentrations of anions were added to study the effect of coexisting anions on the defluoridation efficiency of the gangue-based composite defluoridation agent (GA8) prepared in Example 1. Figure 7 It can be seen that the effects of several anions on the performance of the gangue-based composite defluoridation agent are not obvious, indicating that its adsorption selectivity is good.
[0061] Figure 8 The fluorine removal rates of the gangue-based composite defluorinator (GA8), boehmite (A8) and commercial activated alumina prepared in Example 1 under the optimal adsorption conditions, i.e., the defluorinator dosage is 1 g / L, the defluorinating time is 6 h, the temperature is 30°C, the initial concentration of the fluoride solution C0 is 10 mg / L, and the pH is 3. Combined with the comparison of the residual fluoride ion concentration and the aluminum (hydride) oxide content in different samples, it can be found that the fluorine removal rate of GA8 is slightly lower than that of pure boehmite and slightly higher than that of commercial activated alumina, but only about 7.2% of boehmite is loaded on the gangue, so it has obvious cost advantages; in addition, the fluorine ion concentration in the solution after defluorination by GA8 is 0.24 mg / L, which is lower than 1 mg / L, meeting the national drinking water standard GB 5749-2022.
[0062] During the mining, washing and processing of gangue, it is affected by many factors, resulting in a high content of heavy metal ions, such as lead, mercury, cadmium, chromium, etc., which poses a certain potential risk to human health and the environment. Therefore, when the gangue is used as a resource, the additional impact of the release of these heavy metal ions on the environment must be considered. Through elemental analysis by X-ray fluorescence spectrometer, the gangue-based composite defluoridation agent (GA8) prepared in Example 1 only contains the harmful element lead defined in the national standard GB 5749-2022.
[0063] Table 2 is a comparison of the lead ion concentration in the solution before and after adsorption of the gangue-based composite defluorinator (GA8) prepared in Example 1 under the conditions of a defluorinator dosage of 1 g / L, a defluorinating time of 6 h, a temperature of 30°C, an initial concentration of the fluoride ion solution C0 of 10 mg / L, and a pH of 3. It can be seen that the Pb content in the aqueous solution after adsorption is 0.0073 mg / L, which meets the requirement of the national standard GB 5749-2022 of less than 0.01 mg / L.
[0064] Table 2 Lead ion concentration in fluoride-containing wastewater before and after adsorption
[0065] Adsorption stage Lead ion concentration in solution (mg / L) Before adsorption 0 After adsorption 0.0073
[0066] When conducting actual application tests, the dosage of the defluoridating agent was adjusted from 0.5 g / L to 1 g / L, and the initial solution pH value was adjusted to 3 for optimal adsorption performance, while other parameters remained unchanged.
[0067] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a gangue-based composite defluorinating agent, characterized in that: The following steps are involved: The gangue is mixed with an alkali metal chloride aqueous solution to obtain a suspension, a soluble aluminum salt solution is added at 50-95°C, the pH value is controlled to be 8-11, a coprecipitation reaction occurs, and a gangue-based composite defluoridating agent in which boehmite is loaded on the gangue is obtained.
2. The method for preparing a gangue-based composite defluorinating agent according to claim 1, characterized in that: The concentration of the aqueous solution of alkali metal chloride is 0.01 g / ml to 0.2 g / ml.
3. The method for preparing a gangue-based composite defluorinating agent according to claim 1, characterized in that: The solid-liquid ratio of coal gangue to alkali metal chloride aqueous solution is 0.2g-5g:30ml.
4. The method for preparing a gangue-based composite defluorinating agent according to claim 2, characterized in that: The concentration of aluminum ions in the soluble aluminum salt solution is 10 mol / ml to 100 mol / ml.
5. The method for preparing a gangue-based composite defluorinating agent according to claim 4, characterized in that: The volume ratio of the aqueous solution of alkali metal chloride salt to the soluble aluminum salt solution is 1:
1.
6. The method for preparing a gangue-based composite defluorinating agent according to claim 1, characterized in that: The coprecipitation reaction time is 10min to 4h.
7. The method for preparing a gangue-based composite defluorinating agent according to claim 1, characterized in that: The soluble aluminum salt is one or more of aluminum sulfate, aluminum nitrate, aluminum chloride and alum.
8. The method for preparing a gangue-based composite defluorinating agent according to claim 1, characterized in that: The alkali metal chloride is one of potassium chloride, sodium chloride and lithium chloride.
9. A gangue-based composite defluorinating agent prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the gangue-based composite defluorinating agent according to claim 9 in the treatment of fluorine-containing wastewater, characterized in that: The concentration of fluoride ions in fluoride-containing wastewater is 1.5 mg / L to 10 mg / L, and the addition amount of the gangue-based composite defluoridating agent is 0.5 g / L to 1 g / L.
Citation Information
Patent Citations
Active aluminum oxide fluoride-removal adsorbing material with different surface characteristics as well as preparation method and application thereof
CN103170302A
Method for removing fluoride in drinking water by complexation-coacervation-adsorption with defluorination adsorption material based on aluminium base composite metal oxide
CN103274539A
Prepn. of defluorinating agent for coal gangue
CN1072909A
Metal-doped boehmite as well as preparation method and application thereof
CN107913665A
Device and method for preparing activated aluminum oxide porous material
CN118320802A